HOW TO DRAG A BODY AND OTHER SAFETY TIPS YOU HOPE TO NEVER NEED: Survival Tricks for Hacking, Hurricanes, and Hazards Life Might Throw at You. - STEWART, JULES (Geographical (Geographical Magazine Ltd.), 2021)
By Judith Matloff • Harper Wave Chills, diarrhoea, vomiting, sweating, body aches - all the symptoms endured by Judith Matloffduring an attack of malaria. The author reminds us that mosquito-borne diseases include not only malaria, but dengue fever, Zika, West Nile fever, yellow fever, Chikungunya and encephalitis.